Investigation of food poisoning at syukuran event in Krapyak, Bantul, Yogyakarta 2018 - Gojali, La Karman (BKM Public Health and Community Medicine, 2021)
Objective: On December 3, 2018, Bantul District Health Office received a report from Banguntapan III Primary Health Center that there was suspected food poisoning at a child birth ceremony in Krapyak, Bantul which was held on December 1, 2018. Epidemiological investigations aim to identify the source of the cause, the way of transmission, and provide recommendations for prevention efforts. Method: This study uses retrospective cohort. The definition of a case is a person who experience symptoms of diarrhea, nausea, abdominal pain, fever and headache, either accompanied or without accompanied by other symptoms after obtaining food packages from a Syukuran event in Krapyak, Bantul. Data Collected through case discovery interviews are actively conducted using standardized Questionnaire. Environmental observation and delivery of food samples for bacteriological test have also been conducted at Yogyakarta Health Laboratory . Result: A total of 43 populations are at risk, there are 35 cases with AR= 81.40%. The main symptoms were diarrhea (79.09%), nausea (51.16%) and abdominal pain (27.91%). the pattern of transmission comes from one common source with an average incubation period of 9 hours, the shortest incubation period hours and the longest of 22 hours. The type of food suspected to be the cause of food poisoning is grilled chicken (RR=4.60;p-value=0.01;cl 95%= 1.387-15.277. The result of bacteriological examination are known to have mold/yeast fungi in food samples. Conclusion: The cause of food poisoning is suspected to be sourced from mold/khamir in grilled chicken. improper cooking processes is a risk factor for potential contamination of food. Education on food safety principles in accordance with the minister of health number 1096 needs to be done by Bantul District Health Office and Primary Health Center.